A Common Experience of Ageing: The Social Role of Ancestral Collective Land Tenure Systems in Rural Upland Areas - Olivier Chavanon (Revue de Géographie Alpine)
Collective landholdings (often referred to as ‘common land’) are ancestral land tenure systems that, although little recognised, have endured as institutions in upland areas in France. They play an important role in stimulating rural life, and many of the inhabitants in these areas retain a strong attachment to them. In both the Alps and the Massif Central, these very old systems are of interest today for the various functions they perform, in a not always highly visible but nonetheless very real way. Situated at the intersection of the issues of social cohesion, quality of life, a sensory relationship with the land and intergenerational solidarity, common land contributes to varying degrees, in various forms and under different names, to involving its members in the collective management of local resources. The ageing of common land rights holders is a significant phenomenon that forms part of a fundamental demographic shift. In rural areas, particularly those furthest from urban centres, there is a marked increase in the number of older adults, who make up an ever greater proportion of the general population. These areas are also characterised by the increasing scarcity of certain services and by signs of declining social ties, which often cause consternation and concern among older residents. The virtues of these systems continue to be widely recognised: they provide non-financial benefits that have proven to be useful in a period of inflation; they establish a longer temporal perspective that stands in sharp contrast to the modern culture of immediacy; and they foster relationships with others and with the group that counteract certain effects of isolation and the decline of solidarity and rural amenities. In this article, we aim to understand this attachment to collective landholdings by taking a genuine interest in the words of those who remain involved in passing on these land tenure systems. We explore how common land contributes to the social dynamic of rural areas in France, in particular by enabling older people to retain an active role as part of local life.